PENANAMAN KESADARAN PENTINGNYA MOTIVASI BELAJAR SEBAGAI UPAYA MENUMBUHKAN SEMANGAT BELAJAR PADA SISWA - Aureli Rahmadani, Debby; Rofieq, Ainur; Turmudi Zy, Ahmad (Universitas Islam 45 Bekasi, 2023)
Education is an important aspect in growing and developing one's potential to realize what one dreams of. To achieve your goals you need motivation or encouragement to do something. This seminar activity aims to instill awareness of the importance of learning motivation in fostering enthusiasm for learning in Class 6 students at SDN Karangsegar 02, Karangsegar Village, Pebayuran District, Bekasi Regency. The research method was carried out using observation techniques, interviews and filling out questionnaires from Sardiman figures. The seminar was conducted using lecture and role play methods. The results of the seminar were very significant and could be said to be successful because based on the post test all participants were able to understand the material presented well. It is hoped that after attending this seminar the students will be motivated to be enthusiastic about learning and will ultimately become successful people according to their respective desires.